2021
DOI: 10.3389/fphar.2021.774414
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Effects of Individual Chinese Herbal Medicines on Chronic Kidney Disease

Abstract: The clinical and experimental study into the effects of Chinese herbal medicines on chronic kidney disease has evolved over the past 40 years with new insight into their mechanism and evidence of their clinical effects. Among the many traditional Chinese herbs examined in chronic renal disease, five were found to have evidence of sufficient clinical efficacy, high frequency of use, and well-studied mechanism. They are: Abelmoschus manihot and Huangkui capsule, Salvia miltiorrhiza and its components (tanshinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Salvianolic acid A (SalA), a natural polyphenol compound, is extracted from Salvia miltiorrhiza Bunge and has various potential pharmacological protective roles in NAFLD ( Shao et al, 2021 ). SalA administration clearly attenuated obesity and liver injury induced by a HFD in a mouse model, and significantly diminished lipid accumulation in mouse livers ( Li et al, 2020 ).…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…Salvianolic acid A (SalA), a natural polyphenol compound, is extracted from Salvia miltiorrhiza Bunge and has various potential pharmacological protective roles in NAFLD ( Shao et al, 2021 ). SalA administration clearly attenuated obesity and liver injury induced by a HFD in a mouse model, and significantly diminished lipid accumulation in mouse livers ( Li et al, 2020 ).…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…TGT have been prescribed for patients with CKD for more than 4 decades with sufficient clinical efficacy ( Shao et al, 2021 ). In this study, the efficacy of TGT on the early–and advanced–stage NS rats was further confirmed ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the studies of TCMs have attracted attention owing to its superiority in the treatment of refractory diseases ( Chen et al, 2016b ; Li et al, 2021a ; Shao G. et al, 2021 ; Wang Y. W. et al, 2021 ; Yang and Wu, 2021 ). A variety of compounds isolated from natural products have been protected against renal fibrosis ( Feng et al, 2019b ; Luo et al, 2021 ; Shao M. et al, 2021 ; Zhao et al, 2011 ; Zhou F. et al, 2021 ). Therefore, natural products have attracted more and more attention around the world and are committed to the development of new drugs.…”
Section: Natural Products As An Alternative Therapy Against Tubuloint...mentioning
confidence: 99%